Application of Marker-Based Tracking Augmented Reality of Human Digestive System for Elementary School - Ayu Lestari; Reza Andrea; Syafei Karim (Politeknik Pertanian Negeri Samarinda, 2023)
The digestive system in humans is one of the materials taught in biology subjects. Submission of material about the digestive system in humans is still through conventional media such as blackboards and pictures contained in biology books. While this material about the digestive system is difficult to see directly because most of it occurs in the body. Augmented Reality is a technique that combines two-dimensional and three-dimensional virtual differences into a real sphere. Augmented Reality can be one of the effective teaching materials in elementary schools because of the rapidly advancing technology.